On Some Universal Propositional Proof Systems for Many-Valued Logic - Khamisyan, Artur A. (Mathematical Problems of Computer Science, 2020)
Some uniform Hilbert-like propositional proof system is suggested for all versions of many-valued logic to apply them to 3 versions of 3-valued logic, two of which have only one designated value, and the last one has two designated values